Role of seed-borne inoculum of Rhizoctonia solani in sheath blight of rice - and U.S. SINGH*, P.N. SIVALINGAM, S.N. VISHWAKARMA (Indian Phytopathology, 2006)
Rhizoctonia solani causing sheath blight of rice is reported to survive through soil and collateral hosts. Although it infects seed in field, role of seed-borne inoculum in disease development is not properly understood. During the present investigation seed samples were collected from sheath blight infected field (>90 %) and were stored at room temperature. Symptoms induced by the pathogen on seeds were recorded. No correlation was observed in degree of seed discolouration and isolation frequency of the pathogen. Survival of pathogen and its transmission from seed to emerging seedlings was observed at monthly intervals using paper towel, agar plate and sterilized soil medium methods separately treated with biocontrol agents (Trichoderma harzianum, T. virens and Pseudomonas fluorescens) and fungicide (Carbendazim) treatment. The results showed that (i) paper towel method was most efficient method followed by sterilized soil medium method to assess the transmission of pathogen from seed to seedlings and (ii) the inoculum survived well in seeds from one season to another at room temperature. Biocontrol agents and carbendazim treatments proved that R. solani was internally seed-borne in nature. Inspite of good survival of the pathogen, its transmission to rice plants under field conditions was very poor.